Chinese CO2 emission flows have reversed since the global financial crisis. Issue 1 (December 2017) - Mi, Zhifu; Meng, Jing; Guan, Dabo; Shan, Yuli; Song, Malin; Wei, Yi-Ming; Liu, Zhu; Hubacek, Klaus
Abstract This study seeks to estimate the carbon implications of recent changes in China's economic development patterns and role in global trade in the post-financial-crisis era. We utilised the latest socioeconomic datasets to compile China's 2012 multiregional input-output (MRIO) table. Environmentally extended input-output analysis and structural decomposition analysis (SDA) were applied to investigate the driving forces behind changes in CO2 emissions embodied in China's domestic and foreign trade from 2007 to 2012. Here we show that emission flow patterns have changed greatly in both domestic and foreign trade since the financial crisis. Some economically less developed regions, such as Southwest China, have shifted from being a net emission exporter to being a net emission importer. In terms of foreign trade, emissions embodied in China's exports declined from 2007 to 2012 mainly due to changes in production structure and efficiency gains, while developing countries became the major destination of China's export emissions. China has entered a new normal phase of economic development with a changing role in global trade. Here the authors show that emissions embodied in China's exports declined from 2007 to 2012, while developing countries become the major destinations of China's export emissions.